A collection and abridgement of celebrated criminal trials in Scotland, from A.D. 1536 to 1784 : with historical and critical remarks - Arnot, Hugo, 1749-1786 (HeinOnline. Religion and the law., 1812)
Covers criminal trials in Scotland from 1536 to 1784. Some of the trials included in the collection are those of Archibald Douglass, Robert Logan, Andrew Crichton, John Stewart, John Dickson, Agnes Johnston, Andrew Rutherford, George Clerk, John Ramsay, and James Gray.